NOTARIAL DEED MANDATORY: TRANSFER OF PATENT AND PLANT VARIETY PROTECTION DUE TO AGREEMENT - Elmadiantin,; Y, Annalisa; Febrian, (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research is to analyze the transfer of rights to Patent and Plant Variety Protection due to agreement, carried out in a notarial (notarial deed). It also analyzes the function of notary deed related to the transfer of rights to patent and protection of plant variety. This research is a normative descriptive study, by means of the statute, the conceptual and the historical approaches. The data sources are legal materials of primary, secondary and tertiary classification. They are legal materials containing related laws, regulations, views and developing doctrines. On the basis of the outcomes of the study it can be inferred that the transfer of the right to a Patent whether due to legacy, allowances, wills, grants, written contracts or other causes defensible by statutory regulations, must be done in a notarial (authentic) deed. Meanwhile the transfer of rights to the Protection of Plant Varieties, notarial deed is only required by transfer due to agreement only, not for transfers in other forms. The transfer of rights must be recorded and announced by the rights applicant. If it does not meet the specified recording requirements, the transfer of rights is deemed withdrawn. The notarial deed used in the transfer of Patent and Plant Variety Protection has juridical and economic functions that can deliver legal certainty and preventive defense for the parties. In addition, the notarial deed has the power of proof, that is, the power of physical, formal and material evidence. Besides that it is strong and perfect evidence. It can be concluded that the transfer of patent right and protection of plant variety, for the sake of legal certainty and for verification in the future, needs to be made with a notarial deed. In the future, the procedure for patent registration needs to be immediately determined by the government in order to create legal certainty and law enforcement.